Effective Strategies for Sustainable Soil and Water Management: Enhancing Agricultural Productivity and Environmental Conservation - G.H. Shah (International Journal of Land, 2024)
Soil and water are essential natural resources, and their degradation due to erosion, overgrazing and other factors is ongoing. Water erosion is influenced by climate, topography, vegetation and soil, while wind erosion is affected by wind characteristics, surface features, topography and soil properties. Unsustainable land and water management practices lead to reduced soil fertility, soil loss, lower crop yields, water depletion, deforestation, and diminished biomass. Of the 1386 million cubic kilometres of water on Earth, only 2.5% is freshwater, with most of it locked up, making just a small fraction available for use. Freshwater demand is rising, with agriculture using the most (70%), followed by industry (20%) and domestic use (10%). One kilogram of rice and wheat production requires 2975 liters and 1300 liters of freshwater, respectively. Groundwater is being depleted faster than it can be recharged in some areas, highlighting the need to focus on capturing and storing rainfall and improving soil moisture retention. The integrated watershed management approach is effective for managing soil and water resources, involving all stakeholders in planning and implementation. This includes mapping natural resources, demarcating watershed boundaries, identifying local needs, and developing sustainable action plans. These plans should improve soil and water conservation, enhance productivity, and maintain ecological integrity. Key activities include surface water harvesting, groundwater recharge, soil conservation measures, and promoting diversified farming systems. Monitoring, evaluation, and community involvement are crucial for success. Adopting a scientific approach in integrated watershed management can achieve desired conservation outcomes globally.
Keywords: erosion; ground water recharge; integrated watershed management; natural resources